The issue of confounding in epidemiological studies of ambient air pollution and pregnancy outcomes. Issue 6 (19th February 2009) - Strickland, M J; Klein, M; Darrow, L A; Flanders, W D; Correa, A; Marcus, M; Tolbert, P E
Abstract : Background: Relationships between ambient air pollution levels during pregnancy and adverse pregnancy outcomes have been investigated using one of three analytic approaches: ambient pollution levels have been contrasted over space, time or both space and time. Although the three approaches share a common goal, to estimate the causal effects of pollution on pregnancy outcomes, they face different challenges with respect to confounding. Methods: A framework based on counterfactual effect definitions to examine issues related to confounding in spatial, temporal, and spatial–temporal analyses of air pollution and pregnancy outcomes is presented, and their implications for inference are discussed. Results: In spatial analyses, risk factors that are spatially correlated with pollution levels are confounders; the primary challenges relate to the availability and validity of risk factor measurements. In temporal analyses, where smooth functions of time are commonly used to control for confounding, concerns relate to the adequacy of control and the possibility that abrupt changes in risk might be systematically related to pollution levels. Spatial–temporal approaches are subject to challenges faced in both spatial and temporal analyses. Conclusion: Each approach faces different challenges with respect to the likely sources of confounding and the ability to control for that confounding because of differences in the type, availability, and quality of information required. Thoughtful consideration of these differences should help investigators select the analytic approach that best promotes the validity of their research.